Teachers' Code-Switching in English Language Setting - Siregar, Sabar Hernika (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2023)
This research aimed to determine the most commonly utilized forms and the reasons for using the code-switching strategy in the context of language teaching and learning. The subjects were three teachers who practiced their teaching at different English language courses in Pekanbaru. A qualitative design was employed as the method of the research. Moreover, the data collection was conducted through observation of video and audio recordings of the classes and interviews with the teachers. Based on data analysis, the teachers implemented intra-sentential and inter-sentential code-switching. Furthermore, the results revealed that teachers consciously employed this method for multiple reasons, such as achieving communication goals, managing classrooms, and as a discourse method.